Influence of Parental Involvement and Academic Motivation on Mathematical Achievement: The Role of Students’ Mathematics Interest - Asare, Bright; Welcome, Natalie B.; Arthur, Yarhands Dissou (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The study examines the influence of parental involvement and academic motivation on students' mathematics performance, mediated by students' interest in mathematics. The current study adopts a descriptive-correlational research design. The study population comprises all first-year and second-year senior high students in the Central Region of Ghana. A sample of 290 students was randomly selected from four senior high schools in the Central Region of Ghana. The researcher used stratified sampling techniques to categorize the students into the various courses offered in the schools and employed simple random sampling techniques to select respondents from each stratum for the study. A structured questionnaire was used as a research instrument to collect data from the target population. Analysis of Moment Structures (Amos) version 23 and IBM SPSS version 23 were used as analysis tools for data analysis. The analysis results show that parental involvement, academic motivation, and students' interest in mathematics have a significant positive effect on mathematics achievement. Furthermore, students' interest in mathematics partially mediates the link between parental involvement and mathematics achievement. Finally, students' interest in mathematics partially mediates the connection between mathematics motivation and mathematics achievement. The study recommends that parents must be fully involved in their children's education, especially in their mathematics learning, by providing students with the necessary support to improve their mathematics learning and performance.